Pemanfaatan Teknologi Alat Bantu Rumpon Untuk Penangkapan Ikan Di Perairan Kepulauan Tanimbar - Danyel S. Fuatkait; Zakarias Bacori; Deby M. Kewilaa; Edy Rupilele (Amanisal: Jurnal Teknologi dan Manajemen Perikanan Tangkap, 2025)
This study aims to examine the construction and spatial distribution of fish aggregating devices (FADs) and to identify fishing gears and catch composition associated with their utilization in the Tanimbar Islands waters. The research was conducted from June to August 2025 in Lamdesar Timur and Selaru Island within Fisheries Management Area (FMA) 718, using a quantitative descriptive approach. Data were collected through field surveys, measurements of FAD components, fisher interviews, GPS-based recording of FAD locations, and direct observations of fishing gears and catches. The results show that the FADs used by local fishers are predominantly anchored FADs with simple constructions relying on traditional materials. A total of 34 FADs were distributed in clustered patterns across three main locations, influenced by water depth, oceanographic conditions, and fishers’ local ecological knowledge. FAD utilization involved multiple fishing gears within a single fishing unit, mainly trolling lines, handlines, and kite lines. The catch composition was dominated by yellowfin tuna (Thunnus albacares) and skipjack tuna (Katsuwonus pelamis), with size structures ranging from juvenile to adult individuals. These findings provide a scientific basis for spatial planning of FAD deployment and for regulating their utilization as part of sustainable pelagic fisheries management in archipelagic waters.